Multiculturalism: A Challenge for Cognitive Screeners in Parkinson's Disease. Issue 5 (27th May 2021) - Statucka, Marta; Cherian, Kirsten; Fasano, Alfonso; Munhoz, Renato P.; Cohn, Melanie
ABSTRACT: Background: The Montreal Cognitive Assessment (MoCA) and the Dementia Rating Scale‐2 (DRS‐2) are recommended screeners for Parkinson's disease mild cognitive impairment (PD‐MCI). Cross‐cultural studies examining their diagnostic precision have not addressed cultural bias in a multicultural setting. Objectives: To compare DRS‐2 and MoCA performance between patients born in Canada, the USA, and the UK (Anglosphere group) and immigrant patients born elsewhere (International group). To identify sources of cultural bias by comparing group characteristics, and by assessing the relationships between performance and immigration and socio‐development variables. To examine the diagnostic precision of both tools in detecting PD‐MCI in each group. Methods: We conducted a clinical chart review of advanced PD patients who completed cognitive screeners (MoCA: n = 288, 30% International group; DRS‐2: n = 426, 31% International group). All completed a comprehensive neuropsychological assessment to apply Level II PD‐MCI diagnostic criteria. Results: The International group performed worse than the Anglosphere group on the MoCA and DRS‐2, and the only variable that accounted for some of the group difference was the Historical Index of Human Development, a societal variable, which fully mediated the group effect on the DRS‐2. Diagnostic precision of the MoCA was at chance level in the International group, and was poorer than that of the DRS‐II in this group and that of the MoCA in the Anglosphere group, although these were considered poor. Conclusions: Our results support the recommendation to exert caution in using cognitive screeners to capture PD‐MCI in all patients and particularly with first generation immigrants.